Yan Lv:Visual Narratives and Health Communication (The Journal of Medicine, Humanity and Media, 2024)
With the updating and iteration of technology, there are more possibilities and space for visualisation, and data journalism is increasingly becoming the main form of news presentation nowadays.On 11 July，2024 ，MHM invited Yan Lv, Deputy Director and Editor-in-Chief of Data Journalism at News Peach Update, to share her views on the topic of ‘Visual Narrative and Health Communication’. Editor-in-chief Lv Yan started from why do we use visualisation forms? How do we recognise data? and visual narrative and health communication, she introduced us the history of the development of visual narrative, the importance of visual narrative and the specific application of visual narrative for health communication in practice. From the perspective of communication, visualisation is not just a matter of presentation, but behind it reflects different narratives and different modes of communication. In the last two years, data visualisation can be understood as a methodology, and in the future, it is hoped that more cross-media collaboration and cooperation with participants can be achieved.